Intellectual capital – bank efficiency nexus: evidence from an emerging market - Tu Dq Le; Trang Nt Ho; Nguyen Dat; Thanh Ngo (Cogent Economics & Finance, 2022)
This paper investigates the effect of intellectual capital (IC) and its components on the efficiency of Vietnamese commercial banks from 2007 to 2019 using the two-step Data Envelopment Analysis approach. Banks' efficiency scores are firstly estimated, while the relationship between IC and bank efficiency is examined in the second stage. The results indicate a positive relationship between IC and banks' pure technical efficiency, allocative efficiency, and total cost efficiency. When observing the effect of IC decompositions, the findings show that only human capital enhances all types of bank efficiency. Furthermore, bank size and liquidity risk are significant drivers of Vietnamese bank efficiency. Therefore, our findings suggest that bank managers should focus on intellectual capital, particularly human capital, to strengthen bank efficiency further.
Keywords: G21; G28; G30; 330; bank efficiency; DEA; human capital; Intellectual capital; physical capital; structural capital